MAKNA SHALAWAT: PENAFSIRAN SURAT AL-AHZAB AYAT 56 Telaah Epistimologi Tafsir - Nasrullah Nasrullah; Ahmad Royhan Afif (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2021)
The qur'an as a guide to muslims is a collection oftheoretical and practical topics. If the doctrine is carriedout all, one will have happiness in both the world and theafterlife. The model of understanding the qur'an wasepistimology divided into three periods. First, an ageformative with quasi-critical thought. Second, an era ofaffirmative with ideological reason. And third, thereformative era with critical reason. These three periodshave their own distinctive traits in giving understanding ofverses from the qur'an. Confirming a scripture on aparticular topic requires analysis to confirm its meaning.The same is true of understanding of meaning in the 56thverse of al-ahzab. In people this verse is often the basis forprayer (shalawat). Hence, it was done to give people adeeper understanding. This kind research is libraryresearch. The methods used are qualitative. The dataanalysis used is a descriptive analysis. Basically the ulamaagreed to be the meaning of the verse is a command to readblessings on the Prophet Muhammad, but there aredifferent opinions regarding the law. Imam Syafi'i andImam Ahmad are of the opinion that it is obligatory to hearthe name of the Prophet mentioned, and in the recitation oftasyahud in prayer. Meanwhile, Imam Hanafi and Imam Malik have the opposite opinion. Praying to Prophet isenough to be done once in a lifetime and prayer in tasyahudrecitation in the legal prayer is the sunnah muakkad